Mast Cell-Derived Histamine Mediates Cystitis Pain - Rudick, Charles N.; Bryce, Paul J.; Guichelaar, Laura A.; Berry, Ruth E.; Klumpp, David J. (PloS one, 2008)
Mast cells trigger inflammation that is associated with local pain, but the mechanisms mediating pain are unclear. Interstitial cystitis (IC) is a bladder disease that causes debilitating pelvic pain of unknown origin and without consistent inflammation, but IC symptoms correlate with elevated bladder lamina propria mast cell counts. We hypothesized that mast cells mediate pelvic pain directly and examined pain behavior using a murine model that recapitulates key aspects of IC. Infection of mice with pseudorabies virus (PRV) induces a neurogenic cystitis associated with lamina propria mast cell accumulation dependent upon tumor necrosis factor alpha (TNF), TNF-mediated bladder barrier dysfunction, and pelvic pain behavior, but the molecular basis for pelvic pain is unknown. In this study, both PRV-induced pelvic pain and bladder pathophysiology were abrogated in mast cell-deficient mice but were restored by reconstitution with wild type bone marrow. Pelvic pain developed normally in TNF- and TNF receptor-deficient mice, while bladder pathophysiology was abrogated. Conversely, genetic or pharmacologic disruption of histamine receptor H1R or H2R attenuated pelvic pain without altering pathophysiology. These data demonstrate that mast cells promote cystitis pain and bladder pathophysiology through the separable actions of histamine and TNF, respectively. Therefore, pain is independent of pathology and inflammation, and histamine receptors represent direct therapeutic targets for pain in IC and other chronic pain conditions.